Milkywayzzz Dairy / Muhammad Akid Omar ... [et al.] - Omar, Muhammad Akid; Mohamad Izhar, Fahada Nur; Mohd Kamil, Nur Amira Syahira; Saimi, Nur Ezaini; Ali, Nurul Husna (2021)
There many business man or women out there are having their own successful journey is because of their powerful management and constant plan. It helps in terms of many ways which preventing us from getting strayed far from our own mission, vision and purpose. Business plan that consists of nature of business, strategic location, future prospects, agreement between among members, benefits of the products to customers, business background, partner background, its responsibilities, budgeting costing, our marketing plan which target audience that we aiming, the packing that will attract customers attention, the up-to-date of our business social media and technology, the competition in the same industry, the important of our operation layout, the ingredient that will bring loyalty and trustworthy customers towards us as a new company, the customer relationship that we going to maintain, and the regulation required, our business license, insurance and permit. By having a good process of planning and management system in the business, we believe that the opportunity of loyalty and trust from customer will make our business and product will become much comparable to any other brands in the market. This is the business that we believe will received so much opportunity for expanding business and product in the future, since we produce high quality ingredients in our milks. As for our dairy products, the raw material is important as it will complete the good taste for all of the flavour for our customers. For instance, pure basic milk, matcha, latte, chocolate, colouring and and also sugar. Since there quite huge in term of population, our target audience will be kids, adults and the people will healthy lifestyle. As for further future planning, we hoping that our plan for doing this dairy product will receive good feedback in terms of fast serving, customer satisfaction and the good impact of the milks itself. At the same time, the good relationship of our teamwork will stay and grow well as being a partnership of doing this business dairy together.